Prevention strategies and mental health in Vietnam - Cohen's, Edward (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
This paper addresses the current state of mental health services in Vietnam and provides recommendations for improving the care of people with mental illness. Vietnam’s mental health problems are as prevalent as anywhere else in the world. The country has recently begun an initiative to reform mental health care by improving community-based services for people with serious mental illness. However, mental illness has not been a part of public discourse in Vietnam. There is little recognition of prevalent common mental illnesses (such as depression, anxiety and alcohol abuse) and the care of people with serious mental illnesses relies on either overburdened families with few community resources, or on regional institutions that are not prepared to support recovery. A broad, population-based multi-pronged prevention and health promotion campaign is needed to increase awareness of the public about common mental disorders, address vulnerable populations who are at risk for having mental disorders, and prepare communities to better support people with serious mental illnesses. Received: 30th June 2016; Revised: 15th August 2016; Accepted: 30th August 2016